LINKAGES OF Ca V1.2, GLUTAMATE, AND ODONTOBLAST IN THE MECHANISM OF TOOTH PAIN - Juliyatin Putri Utami (Dentino : Jurnal Kedokteran Gigi, 2020)
Background: Odontoblast is often associated with its role as sensory cell in tooth pain. Odontoblasts have ion channels that contribute to the sensitivity and release of neurotransmitters in odontoblast stimuli that are activated in pulp sensory nerve fibers. Review: Ca V1.2 has unexpected plasticity. In dental injury, the appearance of Ca V1.2 canal in odontoblast is known to change, depend on the duration of injury. The dentinal pulp tissue has the ability to release glutamate, which acts as an intercellular mediator to create neuronal signaling communication between inter-odontoblast and odontoblast- trigeminal ganglion nerve (TG). Discussion: Odontoblasts as a mechanosensitive sensory cell are indicated by the role of the TRP transduction receptor and the release of ATP. Though other canals and active compounds in odontoblast are involved, an important role in delivering the sensation of pain also needs to be known. Odontoblast will communicate with paracrine pulp nerves using ATP and glutamate. Ca2+ enters the odontoblast through activated TRP channels and other ion channels, such as L-type VGCC channels (Ca V 1.2). Followed by the release of glutamate from odontoblast through the glutamate-permeable canal, it can trigger the pulp nerve via glutamate metabotropic receptors (mGluRs). Conclusion: There is involvement of Ca V1.2 and glutamate canals in odontoblast in the delivery mechanism of pain.